2010
DOI: 10.3109/01443615.2010.511724
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer risk perception and predictors of human papilloma virus vaccine acceptance among female university students in northern Nigeria

Abstract: Cancer of the cervix is the most common cancer and the leading cause of cancer mortality among women in sub-Saharan Africa. Although a vaccine against human papilloma virus (HPV) is now available, its acceptance among vulnerable women in developing countries is largely unexplored. We studied cervical cancer awareness and HPV vaccine acceptance among 375 female university students in northern Nigeria. A total of 133 participants knew of HPV (35.5%), 202 (53.9%) had heard of cervical carcinoma and 277 (74.0%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 29 publications
4
43
1
Order By: Relevance
“…Consistently, lack of information about HPV infection and vaccines has been identified as a common barrier to the uptake of HPV vaccines in earlier studies (Kahn et al, 2003;Lee et al, 2007;Iliyasu et al, 2010). Most medical students surveyed in our study were willing to be educated by experts about HPV vaccination and this highlights the importance of medical education on this topic.…”
Section: Discussionsupporting
confidence: 55%
“…Consistently, lack of information about HPV infection and vaccines has been identified as a common barrier to the uptake of HPV vaccines in earlier studies (Kahn et al, 2003;Lee et al, 2007;Iliyasu et al, 2010). Most medical students surveyed in our study were willing to be educated by experts about HPV vaccination and this highlights the importance of medical education on this topic.…”
Section: Discussionsupporting
confidence: 55%
“…Malaysian university students showed relatively low (48%) acceptability of receiving HPV vaccination (Wong and Sam, 2010). Other studies conducted among university students reported between 61% and 84% acceptability of HPV vaccination (Di Giuseppe et al, 2008;Gerend and Magloire, 2008;Lenselink et al, 2008;Iliyasu et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…For example, among Nigerian students, 35.5% were aware of cervical cancer. A high awareness level was reported amongst Polish students who were between 17 and 26 years (98.5%) (Iliyasu et al, 2010;Kamzol et al, 2013). A Dutch study conducted among students between 18 and 25 years old from two university and one non-university technical college found that 94% had heard of cervical carcinoma (Lenselink et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with several other studies which showed a significant positive association be- tween knowledge of college students about HPV and/or cervical cancer and intention to accept HPV vaccine or actual receiving of the HPV vaccine. [23][24][25] Studies had also shown that members of communities at higher risk for HPV infection tend to be less knowledgeable about the transmission mechanisms of HPV and its impacted morbidities. 23,26 In addition to knowledge about causes of cervical cancer, annual health checkup attendance played a significant role in HPV vaccination in the study.…”
Section: Discussionmentioning
confidence: 99%